THE EFFECT OF AUDIOVISUAL-BASED HEALTH EDUCATION ON PARENTS' KNOWLEDGE OF FIRST HANDLING OF FEBRILE SEIZURES IN CHILDREN - Sulastri, Titi; Ningsih, Ratna; Fajri, Hafid Ainun; Hapsari, Dina Carolina; Tambunan, Eviana S; Supartini, Yupi (Jurnal Keperawatan, 2025)
Febrile seizures are prevalent from 3 to 5 years of age. A sudden increase in body temperature is one of the causes of seizures. The role of parents is very influential in managing febrile seizures in children. Adequate parental knowledge can effectively manage febrile seizures. Effective first treatment of febrile seizures in children can prevent post-febrile seizure trauma. Increased knowledge can be achieved through health education, one of the effective health education media is audiovisual media. Analyze the effect of audiovisual-based health education on parents’ knowledge about the first treatment of febrile seizures in children. The type of research used is quantitative with a Quasi-experimental design, a non-randomized pretest, and a posttest with a control group design. The sampling technique used purposive sampling. The sample size used was 82 respondents (41 intervention group and 41 control group) and data analysis using the Wilcoxon signed rank test. Data analysis was carried out with the Wilcoxon Signed Rank Test where the average knowledge score before the audiovisual-based health education intervention with a mean knowledge score was 11.73, while the mean score of knowledge after the intervention was 14.80 with a p-value 0f 0.000 which proves the data is significant. There is a difference in parents’ knowledge about the first treatment of febrile seizures in children before and after being given an audiovisual-based health education intervention.